Pflegeethik zwischen Freizeit und Eigenzeit: Reflexion zum normativen Stellenwert der betreuungsfreien Zeiten in Einrichtungen der stationären Altenpflege - Roth, Benjamin (Ethik in der Medizin, 2024)
Purpose: Care times in retirement homes often only take up a small fraction of the entire day. The question of what scope the residents themselves have to autonomously organize the remaining care-free time and what normative and ethical significance they have has hardly been examined in the German-speaking discourse to date. At the same time, some life reports and studies indicate that nursing home residents usually have no opportunities to organize their free time in a meaningful way. Methods: This article examines the reasons for this situation from the perspective of social and temporal ethics. Reflection on social structures is methodologically at the center of the study. An empirically based institutional ethics approach is developed from the special characteristics of total institutions. This framework is used for the ethical assessment of institutional time structures. Results: In our society, which structures temporality as a reciprocal arrangement between work and leisure time, there are no forms of socially recognized temporality for people without paid work, i.e. not for residents of retirement homes. In the institution of the old people’s home, people’s private time is furthermore institutionally monopolized and completely transformed into institutional time. As a result, people living in old people’s homes are denied their right to individual temporality. Conclusion: In order to counter this problem, it is recommended that Eigenzeit (personal time/selftime) be established as a third social structure of temporality in contrast to working and leisure time. This applies in particular to total institutions. In it and with it, the meaning of life and thus the good life can be realized.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Leisure time; Nursing home ethics; Nursing homes; Own time; Temporality; Total institutions; Working time